Identification of Antibiotic-Producing Bacteria against Selected MDR pathogens from Pharmaceutical Waste Soil - Wahab, Malik Abdul; Bano, Syeda Asma; Tawab, Abdul; Akrama, .; Alam, Sadia; Munir, Sana (Biological and Clinical Sciences Research Journal, 2025)
Antibiotics or antimicrobial agents are the most significant utilized secondary metabolites, which are commonly synthesized by soil bacteria and fungi and found to be effective. Most of the antibiotics used are derived from the soil bacteria and Actinomycetes. Antibiotic resistance poses a serious global health threat, making infections harder to treat, potentially leading to longer illnesses, more complications, increased healthcare costs, and even death. The present research project has been designed to identify and characterize the antibiotic-producing bacteria from the waste soil samples collected from ten different Pharmaceutical Industrial waste soils of Hattar, Haripur, using standard microbiological techniques. Objective: To isolate, identify, and characterize antibiotic-producing bacterial strains from pharmaceutical industrial waste soils, and to evaluate their antibacterial activity against selected MDR pathogens. Methods: Overall, 10 bacterial strains were isolated from waste soil of Pharmaceutical industries to examine their antibacterial activity against four tested pathogens, such as Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus, by using the well diffusion method. Only four bacterial strains out of ten showed high antibacterial activity against these selected MDR pathogens. The isolated bacterial strains were initially identified through Gram staining and biochemical tests. For molecular identification, the MALDI TOF technique was used. Results: The isolated strains S1 and S6 were Enterobacter cloacae, S2 was Enterobacter asburiae, and S8 was identified as Pseudomonas aeruginosa. Then the crude extracts of S1, S2, S6, and S8 were further analyzed by GC-MS to identify the compounds present, in which almost 300 compounds were identified, and out of 300 compounds, some of them (D-Glycero-D-Gulo-Heptonic Acid, D-(+)-Ribonic Acid.Gamma.-Lac, Oxalic Acid, Ethyl Neopentyl E, D-Glycero-D-Gulo-Heptonic Acid, Hentriacontane, Neopentyl Glycol, Strychane, 1-Acetyl-20.Alpha, 3,4-Altrosan, Carbamic Acid, Hydroxy-, Ethyl, etc) were found in previous literature showing anti-microbial, anti-bacterial, anti-fungal, anti-inflammatory, anti-tumor, and anti-cancerous activities. Some new compounds were also detected. Further research of the identified compounds may detect some more effective antibacterial agents against selected MDR pathogens (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus). Conclusion: Bacteria present in waste soil samples of Pharmaceutical industries have the potential to show antibacterial activity against selected MDR pathogens (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus), and biologically active compounds having antibacterial properties may be extracted from these bacterial isolates.